A educação profissional e tecnológica na educação básica e a preparação da pessoa com deficiência intelectual para o mundo do trabalho no município de Manaus - Souza, Leila Maria Carvalho de (2020)
The person with intellectual disabilities to be inserted in the world of work needs a professional preparation that allows him to insert in the formal and non-formal spaces of this space. This research has as general objective to identify the challenges people with intellectual disabilities have in the process of insertion of in the world of work, based on the contributions of professional and technological education/PTE?. It presents as specific objectives: a) to describe about the historical aspects of special education; b) to explain the ontological sense and the categories of work as an educational principle, integral human formation and social belonging; c) develop the educational product from an informative video showing the pedagogical work of the Diofanto Vieira Monteiro School. The research approach is qualitative, being a field research. For the theoretical basis on the objectives we have: Frigotto and Ciavatta (2012), Ramos (2008/2009), Rodrigues and Maranhe (2008), Souza (2014), Freire (2017 ), Pistrak (2018), Veltrone and Almeida (2010), Borges (2017), Barato (2008) among others that address the historical process, ontological meaning of the work and its categorical bases and educational product. The participants of the research were three students with intellectual disabilities, ten parents and/or guardians and four teachers, having as locus the Diofanto Vieira Monteiro State School located in the city of Manaus. The research used semi-structured interviews and participant observation as instruments for data construction. The content analysis was done according to Bardin (2016) who obtained as a result the answer to the problem that referred the research from the question: what pedagogical strategies is the basic teaching education of the Diofanto School using to prepare the person with intellectual disabilities to act in the formal and non-formal spaces of the world of work? From the results of the construction of the data, seven categories were reached: job satisfaction, work need, humanized care in the company, participation of parents, fear of loss of benefit, disbelief in the child's capacity and feeling of social belonging. The results, therefore, allowed us to conclude that the work is important for the development of autonomy and independence of the person with intellectual disabilities.